2019
DOI: 10.3389/fimmu.2019.01324
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum Aggravates the Progression of Colitis by Regulating M1 Macrophage Polarization via AKT2 Pathway

Abstract: Disordered intestinal flora and discordant immune response are associated with the development of ulcerative colitis (UC). Recent work has described the ability of macrophages to undergo repolarization toward a proinflammatory M1 or anti-inflammatory M2 phenotype in response to particular bacterium-derived signals. Fusobacterium nucleatum ( F. nucleatum, Fn ) is a species of intestinal commensal bacteria with potential pathogenicity, but its association with UC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 46 publications
(56 reference statements)
3
63
0
Order By: Relevance
“…Consistently, we found a signi cant ability of the genus Bilophila and Fusobacterium to selectively associate with cases of UC activity/remission. This agrees with the literature that describes a functional role for these bacteria in UC [64,65,66,67] and suggests its potential clinical bene t for an early identi cation of clinical-therapeutic phases of UC [68,69].…”
Section: Discussionsupporting
confidence: 91%
“…Consistently, we found a signi cant ability of the genus Bilophila and Fusobacterium to selectively associate with cases of UC activity/remission. This agrees with the literature that describes a functional role for these bacteria in UC [64,65,66,67] and suggests its potential clinical bene t for an early identi cation of clinical-therapeutic phases of UC [68,69].…”
Section: Discussionsupporting
confidence: 91%
“…The key direct effect induced by disorders of the intestinal microbiota is the destruction of immune system homeostasis in the intestinal tract, which leads to various gastrointestinal diseases (11,12). For instance, Liu et al reported that F. nucleatum aggravates progression of ulcerative colitis (77). Specifically, the bacterium induces M1 differentiation of macrophages in the intestinal mucosal lymphoid tissue; simultaneously, the Th1-associated cytokine IFN-γ is produced by the AKT2 signaling pathway, aggravating the disease (77).…”
Section: Disorders Of Intestinal Flora Affect the Relationship Betweementioning
confidence: 99%
“…For instance, Liu et al reported that F. nucleatum aggravates progression of ulcerative colitis (77). Specifically, the bacterium induces M1 differentiation of macrophages in the intestinal mucosal lymphoid tissue; simultaneously, the Th1-associated cytokine IFN-γ is produced by the AKT2 signaling pathway, aggravating the disease (77). Moreover, in colitis, the intestinal microbiota and specific microbial components activate downstream MyD88 and PI3K pathways through TLR2, to activate IL-10-producing B cells.…”
Section: Disorders Of Intestinal Flora Affect the Relationship Betweementioning
confidence: 99%
“…The differentiation and activation of monocytes or macrophages are the key processes for the development and stability of As (Cochain and Zernecke, 2015). During this illness, monocytes migrate from the bloodstream into the subintima and differentiate into macrophages, which then undergo different polarization states after being stimulated by different signals (Kawano et al, 2019;Liu et al, 2019). The activation states of macrophages are divided into M1 (classical activation) and M2 (alternatively activation) polarizations (Murray et al, 2014).…”
Section: Glutamine Promotes the Polarization Of M2 Macrophagesmentioning
confidence: 99%